2014
DOI: 10.1021/nn505399e
|View full text |Cite
|
Sign up to set email alerts
|

Critical Determinants of Uptake and Translocation of Nanoparticles by the Human Pulmonary Alveolar Epithelium

Abstract: The ability to manipulate the size and surface properties of nanomaterials makes them a promising vector for improving drug delivery and efficacy. Inhalation is a desirable route of administration as nanomaterials preferentially deposit in the alveolar region, a large surface area for drug absorption. However, as yet, the mechanisms by which particles translocate across the alveolar epithelial layer are poorly understood. Here we show that human alveolar type I epithelial cells internalize nanoparticles, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 55 publications
11
80
0
Order By: Relevance
“…Translocation was inversely related to particle size and constant up to 100 ng/cm 2 . Fifty-nm polystyrene particles were transported to 3 % (unmodified) and 8 % (carboxylated) across TT1 alveolar epithelial cell monolayers (Thorley et al 2014). No transport has been detected for the 100-nm particles assessed in parallel in this study.…”
Section: Respiratory Routementioning
confidence: 60%
“…Translocation was inversely related to particle size and constant up to 100 ng/cm 2 . Fifty-nm polystyrene particles were transported to 3 % (unmodified) and 8 % (carboxylated) across TT1 alveolar epithelial cell monolayers (Thorley et al 2014). No transport has been detected for the 100-nm particles assessed in parallel in this study.…”
Section: Respiratory Routementioning
confidence: 60%
“…In a recent study, human LLF increased the uptake of polystyrene NPs by human alveolar epithelial cells, regardless of NP size or surface modification. 43 Moreover, coating MWCNTs 44 or SWCNTs 45 with lipids evoked an increase in intracellular reactive oxygen species (ROS) production.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 However, a recent publication reported that 50 nm nanoparticles enter largely by passive diffusion and are found in the cytoplasm, whereas 100 nm nanoparticles enter primarily via clathrinand also caveolin-mediated endocytosis and are found in endosomes. 27 The contradiction here needs further study to elucidate the possible mechanisms of cellular uptake of nanoparticles. Nevertheless, since the T/C% is closely related to the intracellular accumulation of drugs, drug-loaded nanoparticles could reach relatively higher concentration in tumor cells due to endocytosis.…”
Section: Enhanced Proliferation Inhibition and Apoptotic Induction Ofmentioning
confidence: 94%